Post a New Question


posted by on .

1. make p the subject:

p/p-3= R

2. make R the subject

a= 1- 1/R

  • Mathematics - ,

    You must mean
    p/(p-3) = R
    Rp - 3R = p
    Rp - p = 3R
    p(R-1) = 3R
    p = 3R/(R-1)

    for the second, multiply each term by R, rearrange and factor in a similar way.
    Let me know what you get.

  • To Reiny - ,

    So for the second one, I multiplied each term by R

    aR= R- 1

    but then I got stuck after that... sorry

  • Mathematics - ,

    you are looking for R, so get the R's to one side

    aR - R = -1
    factor out the R
    R(a-1) = -1
    divide both sides by a-1

    R = -1/(a-1)

Answer This Question

First Name:
School Subject:

Related Questions

More Related Questions

Post a New Question